NECESIDADES DE TRATAMIENTO PARA CARIES DENTAL EN ESCOLARES DE ZONAS URBANO Y URBANO MARGINAL DE LIMA - Pineda Mejia, Martha (2000)
The purpose of the present study was to compare the dental caries experience and treatment needs of 678 school children, from 6 to 12 years old, belonging to a urban school and a marginal urban school of Lima city. The data was recorded using OMS codes for Oral Health Surveys. It was determined that urban school children are 5,5 % caries free and marginal urban school children 2,3 % caries free. The greatest significative c. p. o. index was in 6 year old students from the urban marginal zone (7,64) than students from the urban zone (6,17). The greatest c. p. o. index was in 12 year old students from the urban marginal zone (5,66) than students from the urban zone (5, 70). Treatment needs for dental caries are significantly greater (6.47 teeth) for marginal urban children than urban ones (5,47 teeth). ONE SURFACE FILLING was the major treatment required reaching 50 % of total needs, TWO OR MORE SURFACE FILLINGS were 30 % and PULPOTOMY, PULPECTOMY AND TOOTH EXTRACTION together represent 20 % of total needs. Treatment done/treatment need ratio is 0,11 for urban students and 0,07 for marginal urban ones.